Aceruloplasminemia With Psychomotor Excitement and Neurological Sign Was Improved by Minocycline (Case Report). Issue 19 (May 2016) - Hayashida, Maiko; Hashioka, Sadayuki; Miki, Hiroyuki; Nagahama, Michiharu; Wake, Rei; Miyaoka, Tsuyoshi; Horiguchi, Jun
Abstract : Abstract: Aceruloplasminemia is an autosomal recessive disorder of iron metabolism caused by mutations in the ceruloplasmin gene. Its prevalence is 1 in 2, 000, 000 people in Japan. This is a disorder of neurodegeneration with iron accumulation in the brain revealed by MRI. The iron overload induces oxidative stress and generation of reactive oxygen species, which triggers a cascade of pathological events that lead to neuronal death. Intravenous administration of an iron chelator, deferoxamine has been proposed as a method of inhibiting the accumulation of iron. The patient was a 46-year-old Japanese woman. She was diagnosed at the age of 33 years. Deferoxamine was administrated for 6 months but was discontinued due to adverse effects. On admission at the age of 46, psychomotor excitement was acute in onset. The extrapyramidal symptoms reflected iron deposition in the basal ganglia and substantia nigra in the midbrain. Ataxia and a wide-based gate reflected iron deposition in the dentate nuclei of the cerebellum. An antibiotic, minocycline at 150 mg/day successfully ameliorated the clinical symptoms. Minocycline, a second generation tetracycline, has a direct radical scavenging property due to its chemical structure. It has been reported that minocycline is similar to deferoxamine in its ability to chelate iron. Minocycline is also involved in preventing the upregulation of proinflammatory cytokines. The iron-chelating, antioxidant, and anti-inflammatory effects of minocycline were involved in this case.